2021
DOI: 10.7759/cureus.17178
|View full text |Cite
|
Sign up to set email alerts
|

Early Surgical Intervention Followed by Antifungals in Rhino-Orbital Mucormycosis in Patients With COVID-19 Favors Clinical Outcome: A Case Series

Abstract: Mucormycosis is an invasive fungal infection occurring in patients with or without preexisting medical illnesses. During the ongoing coronavirus disease 2019 (COVID-19) pandemic, there have been increasing reports of bacterial and fungal coinfections among some COVID-19 patients with preexisting comorbid illnesses such as diabetes and hypertension, with mucormycosis being one of them. The management of this dreaded fungal infection demands early and prompt surgical intervention to thoroughly remove the infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…[ 58 ] India Case series Single-center 5 [33–70] 20 (1) 100 (5) Singh Y. [ 59 ] India Case series Single-center 13 Nov 2020–Jan 2021 [5–75] 85 (11) 62 (8) Garg R. [ 60 ] India Case series Single-center 7 May 2021 [38–70] 71 (5) 100 (7) Arana C. [ 61 ] Spain Case series Single-center 2 [48–62] 100 (2) 50 (1) Barman Roy D. [ 62 ] India Case series Single-center 2 [39–50] 50 (1) 50 (1) Ashour MM. [ 63 ] Egypt Case series Single-center 6 [41–67] 50 (3) 100 (6) Pal P. [ 64 ] India Case series Single-center 10 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 58 ] India Case series Single-center 5 [33–70] 20 (1) 100 (5) Singh Y. [ 59 ] India Case series Single-center 13 Nov 2020–Jan 2021 [5–75] 85 (11) 62 (8) Garg R. [ 60 ] India Case series Single-center 7 May 2021 [38–70] 71 (5) 100 (7) Arana C. [ 61 ] Spain Case series Single-center 2 [48–62] 100 (2) 50 (1) Barman Roy D. [ 62 ] India Case series Single-center 2 [39–50] 50 (1) 50 (1) Ashour MM. [ 63 ] Egypt Case series Single-center 6 [41–67] 50 (3) 100 (6) Pal P. [ 64 ] India Case series Single-center 10 ...…”
Section: Resultsmentioning
confidence: 99%
“…[ 58 ] 40 (2) 20 (1) 40 (2) Singh Y. [ 59 ] 46 (6) 15 (2) 23 (3) 85 (11) 69 (9) 77 (10) 77 (10) Garg R. [ 60 ] 29 (2) 0 (0) 100 (7) 0 (0) Arana C. [ 61 ] 100 (2) 100 (2) 100 (2) 100 (2) 0 (0) 100 (2) 50 (1) Barman Roy D. [ 62 ] 0 (0) 0(0) 50 (1) Ashour MM. [ 63 ] 17 (1) Pal P. [ 64 ] 10 (1) 30 (3) 80 (8) …”
Section: Resultsunclassified
“…Out of the chosen twenty five such studies, Gupta et al [6] reported 8 patients with hypertension, three with no [9] reported 3 patients suffering from chronic kidney disease, 1 with myelodysplastic syndrome. Barman et al [10] reported patients with hypertension 1 hyperthyroidism 1, diabetes mellitus 8 patients. Nehra et al [11] reported 4 patients with hypertension and 6 with diabetes mellitus .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical tissue removal is crucial in treating mucormycosis, particularly when necrosis and thrombosis impede drug effectiveness . Aggressive debridement of affected areas, especially in rhinocerebral infections, improves survival rates, though such surgical intervention involving otorhinolaryngology, ophthalmology, and neurosurgery is often disfiguring. , Surgery combined with antifungal drugs show promise for rhino-orbital cerebral mucormycosis . However, surgical success varies, limiting its use in disseminated infections.…”
Section: Current Treatment Approachesmentioning
confidence: 99%
“…217,218 Surgery combined with antifungal drugs show promise for rhino-orbital cerebral mucormycosis. 219 However, surgical success varies, limiting its use in disseminated infections.…”
Section: I) Platelet-derived Growth Factor Receptor B (Pdgfrb) Human ...mentioning
confidence: 99%